1998
DOI: 10.1111/j.1471-0528.1998.tb10046.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of very preterm small for gestational age infants: the first nine years of life

Abstract: Objective To determine the influence of intrauterine growth retardation of preterm infants on mortality and cognitive development.Design A nationwide study cohort of very preterm and/or small for gestational age infants (< 32 weeks and/or < 1500 g) born alive in 1983 in the Netherlands. Assessment on neuromotor and cognitive development at five years, and a parental questionnaire on school performance at nine years. Cognitive outcome is defined as handicap for mental and speech-language development, and need f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
93
1
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(106 citation statements)
references
References 16 publications
4
93
1
8
Order By: Relevance
“…Placental insufficiency, which is the most common cause of IUGR, has further been shown to be associated with a considerable perinatal mortality and long-term morbidity (9,10). Multiple follow-up studies of infants with IUGR have shown that fetal IUGR is associated with significant neurodevelopmental disabilities in fine and gross motor skills, cognitive function, activity, self-regulation, language, abstract reasoning, recognition memory, concentration, attention, mood, and school performance in both preterm and term infants (2,(11)(12)(13)(14)(15)(16)(17). Neurostructural correlations with these observed developmental disabilities in the human, which would help to understand the underlying mechanisms, are missing.…”
mentioning
confidence: 99%
“…Placental insufficiency, which is the most common cause of IUGR, has further been shown to be associated with a considerable perinatal mortality and long-term morbidity (9,10). Multiple follow-up studies of infants with IUGR have shown that fetal IUGR is associated with significant neurodevelopmental disabilities in fine and gross motor skills, cognitive function, activity, self-regulation, language, abstract reasoning, recognition memory, concentration, attention, mood, and school performance in both preterm and term infants (2,(11)(12)(13)(14)(15)(16)(17). Neurostructural correlations with these observed developmental disabilities in the human, which would help to understand the underlying mechanisms, are missing.…”
mentioning
confidence: 99%
“…IUGR babies contribute significantly to perinatal and neonatal mortality and morbidity. Ten per cent of low birth weight babies suffer some degree of physical handicap (Gaffney 1994) and 5% show neurodevelopmental delay at age 9 (Kok et al 1998). In utero fetal blood sampling has shown that fetuses with severe IUGR have significantly lower levels of circulating free T4, free T3 and a slight elevation in TSH ( Thorpe-Beeston et al 1991b, Kilby et al 1998.…”
Section: Intrauterine Growth Restriction and Prematurity In Human Prementioning
confidence: 99%
“…Intrauterine growth retardation is associated with an increased risk of perinatal mortality and morbidity and impaired neurodevelopment (Kok et al 1996) 3 . The correct detection of the compromised Intrauterine growth retardation fetus to allow for timely intervention is a main objective of antenatal care.…”
Section: Introductionmentioning
confidence: 99%